Laboratory Investigation Comparing Plaque Removal Efficacy of Two Novel-Design Toothbrushes with Different Brushing Techniques - Wansiri Jansiriwattana; Thitiwan Teparat-Burana (MDPI AG, 2018)
Manufacturers of manual toothbrushes have improved novel brush head designs aimed at achieving good plaque removal even with inadequate brushing technique. This study tested the plaque removal efficacy of two novel designs compared with a flat trimmed toothbrush with different brushing techniques. Two novel-design toothbrushes (Colgate® 360° Surround and Oral-B® Pro-Health™ Clinical Pro-Flex) were tested. The control toothbrush was Butler® GUM 311. Artificial plaque was applied on artificial teeth. Brushing with the modified Bass and horizontal scrub technique was then performed independently. After brushing, the remaining plaque index and Proximal Marginal Index (PMI) were evaluated. With the same brushing technique, there was no statistically significant difference in the mean of the whole mouth plaque scores or PMI among the three different toothbrush designs with neither brushing techniques (p > 0.05). When a comparison was made between the mean PMI of the two brushing techniques in each toothbrush design, Colgate® showed no statistically significant difference with either brushing technique (p > 0.05), but Butler® and Oral-B® showed statistically significantly less PMI with modified Bass technique than with horizontal scrub technique (p < 0.05). No difference in the whole mouth plaque removal efficacy was found among the three different toothbrush designs with either brushing technique.